Evidence of Arthur : fixing the legendary king in factual place and time - Johnson, Flint F. (McFarland & Company, Inc., Publishers, 2014)
"The author explores the question of King Arthur's existence in several original approaches to the subject. Examining the extant literature and other evidence, the author searches for the truth of the who, when and where of King Arthur, concluding that Arthur was an historical entity, placing him in a specific area, narrowing his period of activity"--